2019
DOI: 10.3390/ijms20020409
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum (ER) Stress and Unfolded Protein Response (UPR) in Mammalian Oocyte Maturation and Preimplantation Embryo Development

Abstract: Mammalian oocytes and early embryos derived from in vitro production are highly susceptible to a variety of cellular stresses. During oocyte maturation and preimplantation embryo development, functional proteins must be folded properly in the endoplasmic reticulum (ER) to maintain oocyte and embryo development. However, some adverse factors negatively impact ER functions and protein synthesis, resulting in the activation of ER stress and unfolded protein response (UPR) signaling pathways. ER stress and UPR sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 90 publications
(169 reference statements)
4
86
0
Order By: Relevance
“…There are many more experimental designs and time course experiments that must be conducted to fully understand this outcome, and we are very interested in pursuing outcomes to those stage-specific effects in future experiments. Our results are consistent with the growing conclusion that OA is protective against PA’s effects, specifically in that it alleviates PA-induced ER stress in mouse preimplantation embryos [ 22 27 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There are many more experimental designs and time course experiments that must be conducted to fully understand this outcome, and we are very interested in pursuing outcomes to those stage-specific effects in future experiments. Our results are consistent with the growing conclusion that OA is protective against PA’s effects, specifically in that it alleviates PA-induced ER stress in mouse preimplantation embryos [ 22 27 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Treatment of bovine COCs with FFAs impairs blastocyst development; however, rescue by the unfolded protein response (UPR)/endoplasmic reticulum (ER) stress pathway inhibitor salubrinal identified UPR activation as a major contributor to FFA-dependent developmental decreases [ 21 ]. Studies conducted over the past decade have indicated that the preimplantation embryo is armed with several key stress response mechanisms that, in part, offset the deleterious effects of stress on early development (for review see [ 22 , 23 ]). Most notably, these are the ER stress pathways, which oversee the unfolded protein response (UPR) and activate stress-responsive gene expression patterns in an attempt to allow the early embryo to effectively adapt to and survive both external and internal stressors [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the treatment of cells with the chemical chaperone TUDCA significantly reduced PERK signaling, which was increased in a short period of time under heat stress, and restored the levels of three-germ-layer-specific genes to normal. This finding is consistent with that of a previous study, which showed that relieving ER stress in mammalian cells in vitro had positive effects on embryo survival and development [26]. However, how TUDCA affects embryonic development and protects embryos from heat stress using an in vivo model should be explored in the future.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulation of misfolded and/or unfolded proteins in the ER lumen disturbs its functioning, leading to ER stress. The ERQC (ER quality control system) is in charge of identifying properly folded proteins versus misfolded proteins [45,46]. Properly folded proteins which are approved by the ERQC are channeled for transport to the Golgi complex, while those misfolded proteins are retained in the ER to undergo correct folding or to be targeted for proteolysis by the ER degradation (ERAD) machinery [45,46].…”
Section: Discussionmentioning
confidence: 99%